Manajemen Krisis Pondok Pesantren dalam Mempertahankan Pola Pendidikan Di Tengah Pandemi Covid-19 - Ahmad Zain Sarnoto; Khasnah Syaidah (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study examines the crisis management of Islamic boarding schools in maintaining educational patterns amid the Covid-19 pandemic. This type of research is library research with qualitative methods. Data were collected from library sources with a sociological approach. The theory used is crisis management. The findings of this study are as follows: first, Islamic boarding school-based education is vulnerable to external disturbances, including the Covid-19 pandemic. Second, the pros and cons of Islamic boarding school policies revolve around technical strategies to respond to the pandemic situation as well as in responding to government policies. Third, the urgency of crisis management for Islamic boarding school-based education